Pengembangan gerak dasar berbasis Game Based Learning pada pembelajaran bola besar siswa sekolah dasar - Purnamasari, Ratno; Oktarina, Oktarina; Naviri, Sinta (Trihayu: Jurnal Pendidikan Ke-SD-an, 2024)
This research was motivated by the difficulties of elementary school students in learning physical education and the students' low interest in learning basic movements. This is due to the lack of teacher innovation in providing learning materials and children's locomotor skills are just developing. This research aimed to develop GBL-based basic movements in big ball. The model in this research is the development research model from Borg & Gall. A small-scale trial was carried out on 40 students and one physical education teacher at SDN 4 Pangkalanbaru. Large-scale trials were carried out on 60 students and two physical education teachers students in Pulau Besar. Data collection instruments used questionnaires and observation sheets. Data analysis techniques are descriptive qualitative and quantitative. The basic movements developed include dribbling techniques, passing the ball, stopping the ball and shooting. The product validation results showed an average of 79.7% which met the good criteria, while the game validation results obtained 100%. The eligibility criteria for this product are 99.6% in small-scale tests and 99.5% in large-scale tests. Thus, it can be concluded that this research has produced a GBL-based basic movement for learning big balls for elementary school students which is packaged in the form of an animated video tutorial.